2005
DOI: 10.1007/s10517-005-0499-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Nitric Oxide Synthase and Concentration of Nitric Oxide End Metabolites in the Gingiva under Experimental Pathological Conditions

Abstract: Parameters of NO metabolism in the gingiva were studied during experimental periodontitis accompanied by alloxan diabetes and exogenous hypercholesterolemia. We measured activities of inducible and constitutive NO synthase and concentrations of stable NO end metabolites in rat gingival tissue (total contents of nitrite and nitrate). Under pathological conditions NO-metabolism significantly differed from the control. Treatment with mexidol for 14 days significantly decreased activity of inducible NO synthase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
(6 reference statements)
2
12
0
2
Order By: Relevance
“…The literature includes only a few studies that evaluated iNOS activity in inflamed periodontal tissues. iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The literature includes only a few studies that evaluated iNOS activity in inflamed periodontal tissues. iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data).…”
Section: Introductionsupporting
confidence: 60%
“…NO has been implicated in the pathogenesis of apical infection [45], periapical granulomas [46], and inflamed human dental pulp [47]. Increased iNOS expression in gingiva was shown in periodontitis [20,22,26,28,31], ligature-induced periodontitis [27], experimental periodontitis [30,46], inflamed gingiva [23], localized aggressive periodontitis [21], and recently by our group in aggressive periodontitis (unpublished data).…”
Section: Discussionmentioning
confidence: 81%
“…eNOS was shown to be present in endothelial cells of blood vessels and fibroblasts in gingival tissues 45 . Also, eNOS activity was present in both healthy and periodontitis tissues of rats 9 . eNOS‐mediated NO production is involved in the maintenance of local blood circulation and regulates endothelium‐leukocyte interaction 46 .…”
Section: Discussionmentioning
confidence: 97%
“…NOS, which is produced continuously but at modest levels for short periods of time in endothelium and nerves, is named endothelial NOS (eNOS) and neuronal NOS, respectively, whereas the inducible form of NOS (iNOS) is largely expressed for sustained periods after proinflammatory stimuli 2 . Evidence 3–9 suggests that particularly iNOS‐mediated NO production by resident and inflammatory cells is elevated in plaque‐associated periodontal disease highlighting its contributory role in the pathogenesis of periodontal disease. This elevation is the consequence of induction by bacterial lipopolysaccharide and proinflammatory cytokines such as interleukin (IL)‐1, tumor necrosis factor‐α, and interferon‐γ, which are abundant in a diseased periodontal environment 5 .…”
mentioning
confidence: 99%
“…Непереносимость конструкционных матери-алов чаще всего связана с повышенной чувстви-тельностью к амальгамам -84%, частота непере-носимости сплавов металлов варьирует от 5% до 11%, базисных пластмасс -2-11%, фиксирующих цементов -около 4% [14,26]. Несмотря на развитие дентальной импланто-логии, контингент пациентов, пользующихся съем-ными и несъемными ортопедическими конструк-циями неизменно растет [32].…”
Section: конструкционные материалы в полости рта пациентов вызывающиunclassified